Impact of nanopore-based metagenome sequencing on tick-borne virus detection - Ergunay, Koray; Dincer, Ender; Justi, Silvia A.; Bourke, Brian P.; Nelson, Suppaluck P.; Liao, Hsiao-Mei; Timurkan, Mehmet Ozkan; Oguz, Bekir; Sahindokuyucu, Ismail; Gokcecik, Omer Faruk; Reinbold-Wasson, Drew D.; Jiang, Le; et al. (Frontiers in Microbiology, 2023)
We evaluated metagenomic nanopore sequencing (NS) in field-collected ticks and compared findings from amplification-based assays. Forty tick pools collected in Anatolia, Turkey and screened by broad-range or nested polymerase chain reaction (PCR) for Crimean-Congo Hemorrhagic Fever Virus (CCHFV) and Jingmen tick virus (JMTV) were subjected to NS using a standard, cDNA-based metagenome approach. Eleven viruses from 7 genera/species were identified. Miviruses Bole tick virus 3 and Xinjiang mivirus 1 were detected in 82.5% and 2.5% of the pools, respectively. Tick phleboviruses were present in 60% of the pools, with identities to 4 distinct viral variants. JMTV was identified in 60% of the pools, where only 22.5% were PCR-positive. CCHFV sequences characterized as Aigai virus were detected in 50%, where only15% were detected by PCR. NS produced a statistically significant increase in detection for these viruses. No correlation of total virus, specific virus or targeted segment read counts was observed between PCR-positive and negative samples. NS further enabled the initial description of Quaranjavirus sequences in ticks, where human and avian pathogenicity of particular isolates has been previously documented. In conclusion, NS was observed to surpass broad-range and nested amplification in detection and generate sufficient genome-wide data for investigating virus diversity. It can be employed for monitoring pathogens in tick vectors or human/animal clinical samples in hot-spot regions for examining zoonotic spillover.